2000
DOI: 10.1155/mbd.2000.185
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Mode of Action of the Anti‐Candida Activity of 1,10‐Phenanthroline and its Metal Chelates

Abstract: Metal complexes of malonie acid (metal Mn(II), Co(II), Ni(II), Cu(II), Zn(II), Ag(I)) were prepared and only the Ag(I) complex inhibited the growth of Candida albicans. Malonate complexes incorporating the chelating 1,10-phenanthroline (1,10-phen) ligand showed a range of activities: good (Mn(II), Cu(lI), Ag(I)); moderate (Zn(II)); poor (Co(II), Ni(II)). Metal-free 1,10-phen and Ag(CH3CO2) were also highly active. The metal-free non-chelating ligands 1,7-phenanthroline and 4,7-phenanthroline were inactive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 9 publications
2
72
1
Order By: Relevance
“…Surprisingly their solubility in the solvent was poor and as such they were tested as suspensions. Metal-free phenanthroline has previously been reported to have significant activity against a number of microbes [55] however it was found to be inactive against the microbes used in this study (MIC 90 > 100 lM). There is often variation in sensitivity of different strains of the same species to antimicrobial agents.…”
Section: Antimicrobial Activity Of Coumarin Ligands and Their Ag(i) Cmentioning
confidence: 62%
“…Surprisingly their solubility in the solvent was poor and as such they were tested as suspensions. Metal-free phenanthroline has previously been reported to have significant activity against a number of microbes [55] however it was found to be inactive against the microbes used in this study (MIC 90 > 100 lM). There is often variation in sensitivity of different strains of the same species to antimicrobial agents.…”
Section: Antimicrobial Activity Of Coumarin Ligands and Their Ag(i) Cmentioning
confidence: 62%
“…Metal-based drugs represent a novel group of antimicrobial agents with potential therapeutic applications (Coyle et al 2003a;McCann et al 2000). With the advent of fungal isolates manifesting resistance to azole and polyene drugs (Canuto & Rodero, 2002) there is a requirement for new drugs with alternative modes of action or with the ability to increase the efficacy of existing prescription drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in our laboratories has demonstrated that in RPMI medium at 37 o C the metal-based drugs [Cu(phen) 2 (mal)]·2H 2 O, [Mn(phen) 2 (mal)]·2H 2 O and [Ag(phen) 2 ]ClO 4 (phen = 1,10-phenanthroline) inhibit the growth of C. albicans by around 95% at a concentration of 5 µg/ml (McCann et al 2000;Coyle et al 2003a). It was established that both metal-free phen and the metalphen complexes affect mitochondrial function, retard the synthesis of cytochromes b and c and uncouple respiration.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with 1,7-phenanthroline and 4,7-phenanthroline demonstrated that ligands with chelating ability appeared to be desirable for anti-fungal activity [18]. However, when the 1,10-phenanthroline is replaced by the structurally similar N,N 0 -donor ligand 2,2 0 -bipyridine (bipy) complexes devoid of anti-candida activity are obtained [16].…”
Section: Introductionmentioning
confidence: 99%